Two distinct transmembrane serine/threonine kinases from Drosophila melanogaster form an activin receptor complex. - Wrana, J L (1994)
A transmembrane protein serine/threonine kinase, Atr-I, that is structurally related to receptors for members of the transforming growth factor-beta (TGF-beta) family has been cloned from Drosophila melanogaster. The spacing of extracellular cysteines and the cytoplasmic domain of Atr-I resemble most closely those of the recently described mammalian type I receptors for TGF-beta and activin. When expressed alone in test cells, Atr-I is unable to bind TGF-beta, activin, or bone morphogenetic protein 2. However, Atr-I binds activin efficiently when coexpressed with the distantly related Drosophila activin receptor Atr-II, with which it forms a heteromeric complex. Atr-I can also bind activin in concert with mammalian activin type II receptors. Two alternative forms of Atr-I have been identified that differ in an ectodomain region encompassing the cysteine box motif characteristic of receptors in this family. Comparison of Atr-I with other type I receptors reveals the presence of a characteristic 30-amino-acid domain immediately upstream of the kinase region in all these receptors. This domain, of unknown function, contains a repeated Gly-Ser sequence and is therefore referred to as the GS domain. Maternal Atr-I transcripts are abundant in the oocyte and widespread during embryo development and in the imaginal discs of the larva. The structural properties, binding specificity, and dependence on type II receptors define Atr-I as an activin type I receptor from D. melanogaster. These results indicate that the heteromeric kinase structure is a general feature of this receptor family.